Teorias do jornalismo e o ensino nos cursos do Centro-Oeste: democracia e cidadania como fundamentos obliterados - Santana, Mayara Jordana Sousa (2023)
This study aims to investigate how citizenship and democracy are established as foundational elements of graduate programs in journalism in Brazil. The study involves an analysis of the official documentation of the mentioned programs and the bibliographic references used in Journalism Theory courses offered by journalism programs at federal universities in the Central-West region of Brazil. The general topics of the study are journalism education in Brazil and the institutionalization of journalism as an academic discipline in Brazil. Scientific research on these topics was prompted by the implementation of the new national curricular guidelines (Diretrizes Curriculares Nacionais – DCNs) for journalism programs in Brazil in 2013. These guidelines determined that journalism programs would be considered independent bachelor's degree programs instead of specializations within social communication programs. The problematization of the current context of journalism programs resulted in a theoretical and exploratory study that aims to investigate the foundations and theories of journalism as an academic discipline. This study also pertains to a larger group of studies that interrelate citizenship with democracy. The methodology consists of bibliographic research to build the theoretical framework on the correlation between citizenship, democracy, and journalism. It also includes a documentary analysis of the official documents published by the Ministry of Education (Ministério da Educação – MEC) regarding undergraduate programs in journalism in Brazil. These documents include both basic curricula and DCNs. The analysis aimed to identify mentions of citizenship and democracy, as well as expressions related to these two concepts, in these documents. Finally, a bibliographic analysis was carried out to analyze five books that were listed in the bibliographic references of Journalism Theory courses offered by journalism programs at federal universities in the Central-West region in Brazil. The results demonstrate that citizenship and democracy are foundational elements of the regulations of undergraduate programs in journalism in Brazil since the establishment of the third minimum curriculum in 1969. The first mentions of these concepts were found in the curriculum established during the military dictatorship, a period when citizenship and democracy were not ensured by the Brazilian government. Therefore, these foundational concepts of journalism education in Brazil were not achievable when they were first mentioned. Citizenship and democracy are concepts that are considered ideal in the education of Brazilian journalists, which justifies the implementation of the DCNs in journalism programs in 2013. However, citizenship and democracy, as foundational concepts, are not integrally addressed by the bibliographic references of Journalism Theory courses offered by journalism programs at federal universities in the Central-West region of Brazil. The results of the bibliographic analysis reveal that these concepts are partially addressed in theoretical reflections that aim to explain journalism. Therefore, citizenship and democracy, as foundational elements of journalism theory, have been neglected by the bibliographic references of Journalism Theory courses.